PENGARUH MANAJEMEN LABA TERHADAP KEPUTUSAN INVESTASI DENGAN KOMPENSASI BERBASIS EKUITAS SEBAGAI VARIABEL PEMODERASI - Siti Rokhaniyah (Jurnal Akuntansi, 2019)
Earnings management were positively related to investment decisions. When earnings were overstated, there will be over-invest in property, plant, and equipment, so it can be said that earnings management will lead to direct cost to the investor in the form of inefficient investments decisions (McNichols dan Stubben 2008). The efficiency of investment decision can be enhanced by equity-based compensation (Xian, Chen, and Moldousupova 2011). Granting an equity-based compensation may increase loyalty of the manager, because by this mechanism, manager is part of the owner of the company. So, the investment decisions will be more efficient. Another case if managers are only as an executive without any ownership percentage of the company, they will be more likely to pursue a bonus (agency conflict). This study examined the role of equity-based compensation on the relationship between earnings management to investment decisions. Investment decisions were computed by adding the current period investment, earnings management were proxied by discretionary accruals, and equity-based compensations were measured by the ratio of stock options to total compensations. Equity-based compensation is expected to minimize the inefficient investments decisions as a result of earnings management. With opportunistic earnings management assumption, the presumption was proved by regression analysis that conducted on manufacturing firms in the United States on 2009-2012. Therefore, by 95 percent level of confidence, the findings of this study support previous studies which stated that earnings management were positively related to investment decisions. In addition, there are interaction effects of earnings management and equity-based compensations on the association betwen earnings management on investment decisions. Thus, equity-based compensation can reduce the inefficient investments as a result of earnings management. Keywords: investment decisions, earnings management, equity-based compensations